2007
DOI: 10.1016/j.cardiores.2006.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets of tea polyphenols in the cardiovascular system

Abstract: Tea-derived polyphenols have attracted considerable attention in the prevention of cancer and cardiovascular diseases. In comparison to tumour cells, the elucidation of their molecular targets in cardiovascular relevant cells is still at the beginning. Although promising experimental and clinical data demonstrate protective effects for the cardiovascular system, little information is actually available on how these beneficial effects of tea polyphenols are mediated at the cellular level. By affecting the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(148 citation statements)
references
References 93 publications
1
145
0
2
Order By: Relevance
“…It is thought that polyphenols in tea (eg, phenols and catechins) could account for its benefits in lipid metabolism via antioxidation and inhibition of lipid absorption 6, 11, 37, 38. In vitro green tea has been reported to have ≈2.5 more antioxidant capacity than black tea 39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that polyphenols in tea (eg, phenols and catechins) could account for its benefits in lipid metabolism via antioxidation and inhibition of lipid absorption 6, 11, 37, 38. In vitro green tea has been reported to have ≈2.5 more antioxidant capacity than black tea 39.…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies suggest that greater tea consumption is related to lower cardiovascular disease (CVD) risk2, 3; 1 to 3 or more cups of green or black tea per day is associated with a 20% to 30% risk reduction in stroke and CVD 3, 4. Produced from Camellia sinensis and rich in polyphenols and catechins, green and black tea were reported to exert a cardioprotective effect via antioxidation of proteins, DNAs, and lipids; antiproliferation of vascular smooth muscle cell; anti‐inflammation in cardiovascular cells; and improvement in endothelial functions, blood pressure,5 and lipid profile 6…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that major tea constituents play a significant role in prevention and delay of various metabolic disorders like diabetes, obesity, hypertension, cancer and cardiovascular disorders (Stangl et al 2007). Thus, exploration of new economical and reliable sources other than tender tea shoots (two leaves and apical bud) is highly required.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Osada et al (2001), catechins inhibited cholesterol oxidation and the formation of 7β-hydroxycholesterol, 5β-epoxycholesterols and 7-keto cholesterol with the addition of catechins to LDL, and it is suggested that the radical scavenging action was responsible for it. Stangl et al (2007) detailedly reviewed on the mechanisms of catechin action in the prevention of cardiovascular diseases. A recent study (Upaganlawar and Balaraman, 2010) reported green tea with vitamin E reduced OS during myocardial infarction (MI) in rats.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%